2005
DOI: 10.1897/04-580r.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, biotransformation, and mode of action of arsenic in two freshwater microalgae (Chlorella sp. and Monoraphidium arcuatum)

Abstract: The toxicity of As(V) and As(III) to two axenic tropical freshwater microalgae, Chlorella sp. and Monoraphidium arcuatum, was determined using 72-h growth rate-inhibition bioassays. Both organisms were tolerant to As(III) (72-h concentration to cause 50% inhibition of growth rate [IC50], of 25 and 15 mg As[III]/L, respectively). Chlorella sp. also was tolerant to As(V) with no effect on growth rate over 72 h at concentrations up to 0.8 mg/L (72-h IC50 of 25 mg As[V]/L). Monoraphidium arcuatum was more sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
122
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 199 publications
(134 citation statements)
references
References 37 publications
8
122
2
2
Order By: Relevance
“…The studies showed that less than 0.01% of arsenate added could be incorporated into algal cells [2]. The growth of M. aeruginosa was markedly inhibited by arsenate, and the inhibition was greater at high arsenate concentration than at low concentration (Fig.…”
Section: Aeruginosamentioning
confidence: 96%
See 3 more Smart Citations
“…The studies showed that less than 0.01% of arsenate added could be incorporated into algal cells [2]. The growth of M. aeruginosa was markedly inhibited by arsenate, and the inhibition was greater at high arsenate concentration than at low concentration (Fig.…”
Section: Aeruginosamentioning
confidence: 96%
“…1). The toxicity of intracellular arsenite, derived from arsenate in medium, was speculated to be one reason for the inhibition of arsenate [2]. Moreover, arsenate could induce the accumulation of reactive oxygen species (ROS) in the cells of cyanobacteria [25], and overaccumulation of ROS could result in cell death [26].…”
Section: Aeruginosamentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its structural similarity with As(V), 10 the influence of P on microbial As metabolisms has been extensively studied and primarily focused on As(V) accumulation and toxicity. 11,12 Besides affecting As(V) uptake, P can further influence the subsequent As detoxification process, i.e. As(V) reduction.…”
Section: ■ Introductionmentioning
confidence: 99%